The economic convergence in ASEAN and prospects for a monetary union - Mongid, Abdul (The Philippine Review of Economics, 2006)
ASEAN countries have deliberated on the feasibility of a monetary union that seeks to set a common currency in the region. This is in accordance with the second declaration of the Bali Concord reaffirming the intention toward economic cooperation and integration. This study investigates the possibility of convergence of economic and monetary variables among ASEAN member countries by using cointegration methodology on economic data. The study found that most monetary data are not converged. Based on the results, monetary union in the form of a currency union is not yet feasible. However, ASEAN countries should start to apply a loose monetary union and dare to step onward and act consistently.